PERBEDAAN KADAR TIMBAL (Pb) DALAM DARAH SEBELUM DAN SESUDAH PEMBERIAN AIR KELAPA HIJAU (Cocos nucifera L) PADA PEKERJA PENGECATAN DI INDUSTRI KAROSERI SEMARANG - Chesaria Candra Cahyani; Onny Setiani; Yusniar Hanani Darundiati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Exposure of lead can cause health problems for humans. Paint is one source of lead (Pb) exposure. Green coconut water has a potential to reduce concentration of lead in blood. The purpose of the study was to determine differences in the concentation of lead (Pb) in the blood before and after treatment of green coconut water (Cocos nucifera L) on the body of a worker painting industry Semarang. The design of the research was quasi experimental, with of one group pre-test - post-test design. The population in this study was all painting workers in carrosserie factory at Semarang who were included in inclusion criteria. Collecting data used tool such as questioner. Lead examination in the blood was measured by AAS (Atomic Absorption Spectrophotometer). The results showed the average of concentration of lead in the blood of workers before being treated was 35.0091 µg/dl and after being treated is equal to 9.0089 µg/dl. Age of respondents ranged between 19-54 years, the lowest working lives of respondents was 1.2 months and the highest is 30 years, amounting to 96.9% of respondents have a long work more than 40 hours and the majority of respondents (56.3%) had the smoke habit. Based on Wilcoxon test found significant value 0.0001 (p> 0.05) means that there is a significant difference between the levels of lead in the blood of workers in industrial painting section Semarang body of water before and after giving the green coconut (Cocos nucifera L).